The Story of Kathy Knowles: The Silent Warrior in Library Development in Contemporary Ghana - Adjah, Olive A. (Ghana Library Journal, 2004)
A number of expatriates have played important roles in the history of the development of libraries in Ghana. This paper discusses the contribution of Kathy Knowles, a Canadian Nurse, who lived in Ghana between 1989 and 1992. It introduces Kathy as a "silent warrior" and highlights the innovative methods she employs to promote reading and literacy among the socially disadvantaged persons. The paper concludes with the view that Kathy is indeed filling vacuums in the provision of library services in Ghana.